2012
DOI: 10.1111/j.1758-8111.2012.00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weight loss after gastric bypass surgery on thyroid function in euthyroid people with morbid obesity

Abstract: Obesity is positively associated with serum thyrotropin (TSH) concentrations at the high end of the normal range. The relationship between weight loss and thyroid function is less clear and studies to date have yielded inconsistent results. Our aim was to describe changes in thyroid function in obese people in relation to durable and significant weight loss after Roux-en-Y gastric bypass (RYGB) surgery. We recorded percentage of excess weight loss (% EWL), serum TSH and free thyroxine (fT4) before and median 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Most [12][13][14][15][16], but not all [17][18][19], studies evaluating the variation of TSH after bariatric surgery have also shown a decrease of TSH after the procedure. Moulin de Moraes et al [13] reported that in 54 euthyroid patients submitted to RYGB there was a significant decrease in TSH that was not correlated to percent change in BMI and a significant decrease in FT3 but not in FT4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most [12][13][14][15][16], but not all [17][18][19], studies evaluating the variation of TSH after bariatric surgery have also shown a decrease of TSH after the procedure. Moulin de Moraes et al [13] reported that in 54 euthyroid patients submitted to RYGB there was a significant decrease in TSH that was not correlated to percent change in BMI and a significant decrease in FT3 but not in FT4.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the impact of bariatric surgery on FT4 levels is more controversial with different studies reporting decreasing [22], A: Univariate analysis of TSH variation at 12 months after bariatric surgery. B: Multivariate analysis of TSH variation at 12 months after bariatric surgery BMI body mass index, TSH thyroid-stimulating hormone, FT4 free thyroxine, FT3 free triiodothyronine stable [12][13][14]18], or increasing [17,19] levels after bariatric surgery. We must highlight that this is the largest study to date evaluating the effect of bariatric surgery on TSH variation in euthyroid patients with morbid obesity and that our evaluation was not restricted to a type of surgery, including three of the most common surgeries for treatment of morbid obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparable results were described by Chikunguwo et al [16]in a 12-month follow-up study which enrolled 86 euthyroid obese patients after RYGB or adjustable gastric banding surgery. On the contrary, MacCuish et al [17]reported that weight loss after RYGB was accompanied by a significant increase in serum FT 4 but no change in TSH in 55 euthyroid individuals with morbid obesity. Vettor et al [18]observed a significant decline in both FT 3 and FT 4 , while TSH remained unchanged in an 18-month follow-up study which enrolled 10 morbidly obese subjects receiving biliopancreatic diversion surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Improved thyroid status has been reported among obese patients following other bariatric surgical procedures [4][5][6][7][8][9][10][11][12], while few studies have been published on the effect of LSG on thyroid status [13][14][15].…”
Section: Introductionmentioning
confidence: 99%